Efeitos da dose única de parecoxibe sobre a morte celular em rins de ratos submetidos à hemorragia aguda - Silva, André Carnevali da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Introduction. Parecoxib has proven analgesic efficacy in the treatment of pain, however its adverse renal effects are unclear. The cyclooxygenase-2 inhibitors generate damage to the kidney through renal vascular dynamic changes, on the other hand they block the inflammation, and it is believed that inflammation is related to kidney damage. In cases of renal hypoperfusion, as in situation of hemorrhage and hypovolemia, there is direct reduction of nutrient input and ischemia stimulates the production of inflammatory mediators. The aim of this study was to evaluate whether a single dose of parecoxib influences the occurrence of apoptosis or necrosis in kidneys of rats submitted to hemorrhage. Methods. Twenty-four adult Wistar rats anesthetized with sevoflurane were randomly distributed into four groups (n=6): placebo/ no hemorrhage (plac/ nh), parecoxib/ no hemorrhage (PCX/ nh); placebo/ hemorrhage (plac/ H) and parecoxib/ hemorrhage (PCX/ H). The animals received single intravenous bolus of parecoxib, 20mg/kg, or placebo according to the group distribution. The animals in groups with hemorrhage suffered bleeding corresponding to 30 % of volemia during 20 min. Eighty min after the administration of parecoxib or placebo and 30 minutes after the end of the hemorrhage period, bilateral nephrectomy was performed to assess necrosis or apoptosis by flow cytometry. Results. The groups which received parecoxib (PCX/ nh and PCX/ H) showed a higher amount of renal necrosis, minor amounts of apoptosis, and higher amount of viable cells by flow cytometry. Conclusion. A single dose of parecoxib generated renal necrosis, but was associated with kidney protection against apoptosis and with increased number of viable cells early after hemorrhage

Introdução: O parecoxibe tem comprovada eficácia analgésica no tratamento da dor, entretanto seus efeitos adversos renais não estão esclarecidos. Se por um lado os inibidores da ciclooxigenase-2 geram danos ao rim por alterar a dinâmica vascular renal, por outro lado bloqueiam a inflamação, e admite-se que a inflamação esteja relacionada com prejuízos ao rim. Em casos de hipoperfusão renal, como em situação de hemorragia e hipovolemia, há diminuição direta do aporte de nutrientes e a isquemia estimula a produção de mediadores inflamatórios. O objetivo desta pesquisa foi avaliar se a dose única de parecoxibe influi na ocorrência de apoptose ou necrose em rins de ratos submetidos à hemorragia. Métodos: Vinte e quatro ratos Wistars adultos anestesiados com sevoflurano foram distribuídos aleatoriamente em quatro grupos (n=6): grupo placebo/ sem hemorragia (plac/ sh); grupo parecoxibe/ sem hemorragia (PCX/ sh); grupo placebo/ hemorragia (plac/ H) e grupo parecoxibe/ hemorragia (PCX/ H). Receberam bolus endovenoso em dose única de parecoxibe, 20mg/kg, ou placebo de acordo com a distribuição por grupos. Os animais dos grupos com hemorragia sofreram sangria correspondente a 30% da volemia durante 20 min. Após 80 min da administração do bolus de parecoxibe ou placebo e 30 min do fim da hemorragia, foi realizada nefrectomia bilateral para avaliação de necrose ou apoptose pela citometria de fluxo. Resultados: Os grupos que receberam parecoxibe (PCX/ sh e PCX/ H) apresentaram maior quantidade de necrose, menor quantidade de apoptose e maior quantidade de células viáveis renais pela citometria de fluxo. Conclusão: A dose única de parecoxibe gerou necrose renal, mas associou-se à proteção do órgão contra apoptose e à maior quantidade de células viáveis precocemente após hemorragia
Effects of single dose of parecoxib on cell death in kidneys of rats submitted to acute hemorrhage
Keywords: Apoptose; Necrose; Medicamentos - Dosagem; Anestesicos - Efeito fisiologico; Rins - Doenças; Apoptosis